Barodontalgia among pilots: a cross-sectional study - Abidin, Sulhi; Mat Daud, Muhamad Sharifuddin (2021)
The questionnaire was distributed to all active military pilots in Malaysia: it consists of several parts; demographic data, dental care, and dental pain